International Jurisdiction in Diesel Emissions Claims under the Brussels Ibis Regulation - Monico, Rebekka (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The broke of the Dieselgate in the Unites States in September 2015 gave rise to a multitude of cross-border claims brought by the final purchasers/consumers against the car and engine manufacturers involved in the emissions scandal. The article examines which rules on jurisdiction laid down in Regulation 1215/2012 apply to cross-border Dieselgate-related claims with particular regard to the interpretative issues which arise with regard to the forum delicti under Art. 7 n. 2 of the Brussels Ibis Regulation.
Keywords: Dieselgate; International jurisdiction; Brussels Ibis Regulation; Place of the event giving rise to the damage; Place of the damage